The description of concentration, viability, motility and normal sperm form in patients with varicocele. - Dicky M. Rizal Dicky M. Rizal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Varicocele was one of the causal factor s of infertility which related with the abnormality of sperm.Objective: The aim of this study was to know the description of concentration, viability, motility and normal sperm form in patient with varicocele, and different level of that result between three grades of varicocele.Method: This study was a retrospective-analytic study on the medical record data of patients with varicocele at Fermata Hati Infertility Clinic during January 2001-July 2002. The concentration, motility, viability and sperm normal form were evaluated and analized.Results: The results showed that 103 patients with varicocele were found, consisted of 87.4% patients with left varicocele, 1.9% right varicocele, and 10.7%. bilateral. The incidence of decreased concentration 38.8%, decreased motility 63.7% sibjects and viability 51.6%. There were decreased mean ratio of motility Ix = 41.12% for (a) category and x=16.37% for (b) category), and viability (x =73.5% life). Analysis by one way ANOVA showed that no significant differences of mean between each variable of three grades of varicocele (p>0.05).Conclusion: Abnormality in the parameters of sperm analysis was found in varicocele cases, but the grade of varicocele was not related to the concentration, motility, viability and normal sperm form.Keywords : varicocele-sperm motility-sperm viability-sperm form-infertility.